Mostovi med jatami galaksij - Čeplak Mencin, Fedja (Matrika, 2021)
At the end of the 20th century scientists discovered, that there is much less (almost 50 %) baryonic matter in our Local Universe than in the Early Universe. With the help of simulations of large regions of space, they found out that in the past, most of the baryonic matter was in the < 10?$^5$? K temperature range. At the present, almost 40 % of the total baryonic matter is in the form of filaments of warm-hot gas - enormous structures, that connect different galaxy clusters, with temperatures between 10?$^5$?-10?$^7$? K. This type of gas is very sparse, so it is almost impossible to detect it in absorption or emission spectrum. One of few posibilities for its detection are special systems, where short filaments connect two nearby galaxy clusters.
Keywords: cosmology; galaxy clusters; intergalactic matter; jate galaksij; kozmologija; medgalaktična snov; Universe; vesolje